MATERNAL AGE INCREASES THE RISK OF DOWN SYNDROME: A CASE-CONTROL STUDY IN YOGYAKARTA, INDONESIA - Zevanya, Evita; Indrarto, Wikan; Lestari, Dewi; Widagdo, The Maria Meiwati (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Background: Down syndrome incidence increases year to year and ranks first in birth defect cases in Indonesia. Down syndrome birth may burden family physically, socially, economically, and emotionally. The most common risk factor associated to Down syndrome is maternal age. Objective: This research is conducted to understand the association between maternal age and parity as the risk factors of Down syndrome births. Methods: Analytical observation design with case-control approach is used in this study. Bivariate and multivariate analysis were calculated using Chi-Square and binary logistic regression test. Results: This research’s results showed significant association between maternal age as risk factor with the incidence of Down syndrome (p-value < 0.001) and no significant association between parity with the incidence of Down syndrome (p-value > 0.05) in Yogyakarta, Indonesia. Mothers aged ? 35 years have 18.82 greater risk to give birth Down syndrome baby compared to mothers aged < 35 years (OR=18.82). The mean of maternal age when birth Down Syndrome children was 35.1 years old. Biological ovarium aging hypothesis presumed cause higher probability of chromosomal segregation failure during oocyte meiosis. Advanced maternal age naturally causes biological ovarium aging. Biological ovarium aging may caused or influenced by hormonal imbalance, limited oocyte pool, oxidative stress, change of spontaneous abortus mechanism, and genetic abnormality or mutation. No significant association between parity with the incidence of Down Syndrome (p-value=0.0689). Conclusion: Mothers with age of 35 year or older are the only the risk factor for having child with Syndrome Down in this research, with 18.82 more greater risk than mothers under 35 years old. The mean of maternal age when birth Down Syndrome children was 35.1 years old.